Development of Problem Solving Training Program Based on Acceptance and Commitment Therapy in Adolescents and Young Adults with Amphetamine Addiction - กำเลิศ สุภาภรณ์; แหนจอน จุฑามาศ; ทรัพย์วิระปกรณ์ วรากร (Journal of The Royal Thai Army Nurses, 2019)
The aimed of this research were to develop the Problem solving training program based on Acceptance and Commitment Therapy in adolescents and young adults with amphetamine addiction (PST-ACT) and to test the effectiveness of the PST program. The sample consisted of 30 men with amphetamine addiction, in Pianpitak Drug Free House, Amphoe Phanom Sarakham, Chachoengsao, age 14-25 years old. The sample was randomized by using random assignment and matching into two groups: an experimental and a control group, 15 persons in each group. The research instruments were 1) the PST-ACT program, which was design by the researcher. 2) The Social Problem Solving Inventory Revised-short from: SPSI-R short from Thai version. 3) The Wisconsin card sorting (WCST-64). The experimental group received the PST program 3 times per week and the control group received the drawing activities during the same period. The assessments were done in 3 phases: pretest, posttest and follow-up. The data were statistically analyzed by utilizing a repeated measures analysis of variance and paired-different test by Bonferroni method. The results revealed that the interaction between the experimental methodology and the dura amphetamine addiction in the experimental group had the mean score of problem solving higher the those in the control group in the posttest and follow-up with statistically significant at .05 level. Adolescents and young adults with amphetamine addiction in the experimental group had the mean score of problem solving in the posttest and follow-up higher than the pretest with statistically significant at .05 level. It was concluded that the PST-ACT program had the effectiveness on enhancing problem solving in adolescents and young adults with amphetamine addiction.